Calpain 10 gene SNP-44 T>C polymorphism in type 2 diabetes mellitus of Bangladeshi origin - Mir, Salma (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2010